Control design to minimize the number of bankrupt players for networked evolutionary games with bankruptcy mechanism - Liyuan Xia; Jianjun Wang; Shihua Fu; Yuxin Gao (AIMS Mathematics)
This paper analyzed the strategy optimization problem of networked evolutionary games (NEGs) with bankruptcy mechanism. The main objective was to design a state-feedback control such that the number of bankrupt players is minimized. First, an algebraic expression was formulated for this type of NEGs by the semi-tensor product of matrices, based on which the sets of profiles with different numbers of bankrupt players are defined. Second, a desired profile set in which the number of bankrupt players is no higher than a given value was obtained, and the convergence region of this set was calculated. Third, for any profile in the convergence region of the desired set, we propose a controller design method to minimize the number of bankrupt players. Finally, an example is given to illustrate the validity of our results.